2021
DOI: 10.1108/bij-04-2021-0190
|View full text |Cite
|
Sign up to set email alerts
|

Identification of specific metrics for sustainable lean manufacturing in the automobile industries

Abstract: PurposeThis study explains the importance of performance measures and identifies the specific performance measures of sustainable lean manufacturing (SLM) for automobile industries. Awareness towards sustainability and continuous improvement approaches demand monitoring of the sustainable lean impact on organization/industry, and hence, identifying the specific performance metrics is of peak importance.Design/methodology/approachIn this study, specific metrics for social, economic and environmental performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 72 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…An implementation framework diagram has been made available in a number of scholarly papers (Schulze and Dallasega, 2023;Kaswan et al, 2023;Mathiyazhagan et al, 2022;Bhadu et al, 2022;Mostafa et al, 2013). Using a framework, Kumar et al (2022) and Chauhan and Singh (2012) evaluated the condition of LM in the manufacturing sector. Chaple et al (2018a) have used the TISM technique to present a model of the lean implementation challenges.…”
Section: Existing Methods Research Gaps and Contributions Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…An implementation framework diagram has been made available in a number of scholarly papers (Schulze and Dallasega, 2023;Kaswan et al, 2023;Mathiyazhagan et al, 2022;Bhadu et al, 2022;Mostafa et al, 2013). Using a framework, Kumar et al (2022) and Chauhan and Singh (2012) evaluated the condition of LM in the manufacturing sector. Chaple et al (2018a) have used the TISM technique to present a model of the lean implementation challenges.…”
Section: Existing Methods Research Gaps and Contributions Of This Studymentioning
confidence: 99%
“…As a result, industrial companies of all types have become conscious of the need to improve their performance in the face of competition and have adopted LM to accomplish continuous development. According to the research of Kumar et al (2022), Bashar et al (2021), Yadav et al (2020) and Alkhoraif et al (2019) LM has benefitted a wide spread of industry variations mainly modifying the operational parameters such inventory cost, handling cost, quality control cost, by keeping them as low as possible. This manufacturing practice is viewed as a fast-growing norm in developing countries with emerging economy for its wellpaid returns (Mathiyazhagan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Lean management distinguishes between five principles that apply to both employees and the entire organization at every level [41]:…”
Section: Lean Management Is Fully Integrated Into Industrymentioning
confidence: 99%
“…2.2.1 Organizational support. Organizational support incentivizing innovation positively results in organizational innovation implementations (Kumar et al, 2021;Patel et al, 2021). For management training of Chinese manufacturing companies, organizational support is vital because the resources needed for LM implementation will be more widely accessible and provide backup to incentivize employees to adopt LM practices.…”
Section: Organizational Factorsmentioning
confidence: 99%
“…In stakeholder theory, organizations execute actions to meet the needs of their primary stakeholders. Among various stakeholder groups, customers are considered to be the most important stakeholders of a company (Gandhi et al, 2021;Kumar et al, 2021). Numerous studies have revealed a positive relationship between customer stress and a company's environmental activities (Agyabeng-Mensah et al, 2021;Yang et al, 2021).…”
Section: Environmental Factorsmentioning
confidence: 99%